(3TQM GdcGajIs - (3GdESJQGHGPj GdSefGFj GdfLaj GdQVj, GdQVj, fLe GdOjf, eMeO Hf GdMSf, fMh (B686 (3g`s
(3ChdgG (B:s
(3GdMeO ddg aGWQ GdSeGhGJ hGdCQVjf (B... (3bhdg GdeHfi eG fGSH eHfi GdCUd Ch hbY ZjQ eQJH ; GdeHfi ceG eQ aj HGH GdeYQH VQHGf eHfj dabOGf ehLH GdEYQGH GdPj gh GdJQcjH cGdCSeGA GdeYOhOI (B...s
(3BNQgG (B:s
.. (3ceG MPaJgG eY GdcdedI GdefaUdI fMh GZRhG GdcaGQ hGQehG GdQV hcPG GZRf hGQpeqf jG GeQCI JMPa GdJGA ceG MPaJ aj GZRj GdLjT hGQej GdYQV hHVe GdhGh hGdeaJhM bHdgG fMh GMThf (B...s
(3JHUQI GdeDda (B:s
(3GdMSf Hf eMeO Hf TQaTGg GdGSJQGHGOj h eMeO Hf GdMSf QVj GdOjf GdGSJQGHGPj TQMG GdcGajI (B!s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\86s
(3Ta GdXfhf (B2\1370s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs